A kind of carbon dot modified fluorescent fiber and preparation method thereof

Through the preparation of carbon dot modified fluorescent fibers, the problem of fluorescence quenching in traditional fluorescent fibers in thermoplastic processing is solved, and the fluorescent fibers that are resistant to high temperature and high stability are achieved, which significantly improves the anti-counterfeiting efficiency and safety of film materials. .

CN115584626BActive Publication Date: 2024-12-24WUHAN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211207853.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-30
Publication Date
2024-12-24
Estimated Expiration
2042-09-30

AI Technical Summary

Technical Problem

The fluorescence of traditional fluorescent fibers is easily quenched during thermoplastic processing, and is easily affected by external conditions such as light, solvents, acids and alkalis, resulting in loss of fluorescent properties and being unable to be applied to film packaging materials. It lacks anti-counterfeiting materials that are resistant to high temperature and high stability. .

Method used

The preparation method of carbon dot modified fluorescent fiber is adopted. By synthesizing carbon dots of 5-10nm and modifying the surface of the fiber substrate, a high-temperature resistant fluorescent fiber is formed. The reaction is carried out by using a high-pressure reactor and a polytetrafluoroethylene lining to combine with amino groups. By reacting the modification and cross-linking, carbon dot modified fluorescent fibers with a length of 2-6 mm were prepared.

Benefits of technology

It realizes the high temperature stability and long life of fluorescent fibers, is difficult to separate anti-counterfeiting information, and the low mobility of fluorescent substances, which significantly improves the anti-counterfeiting efficiency and safety of film materials, and has huge market potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003873475930000011
    Figure HDA0003873475930000011
  • Figure HDA0003873475930000021
    Figure HDA0003873475930000021
  • Figure HDA0003873475930000031
    Figure HDA0003873475930000031
Patent Text Reader

Abstract

The present invention discloses a carbon point modified fluorescent fiber, which is composed of the following raw materials in parts by weight: 0.1 to 1 part of carbon point modified fluorescent fiber; 1 to 20 parts of compatibilizer; and 1 to 5 parts of plasticizer. The anti-counterfeiting information marker of the present invention is difficult to be separated, and the nano organic fluorescent fiber is obtained by fluorescent labeling in a chemical loading manner. The migration rate of the fluorescent substance used is extremely low, and it is impossible to use existing analytical instruments for sampling separation and component analysis. It has extremely high anti-counterfeiting efficiency in the field of thin film materials, further enhances technical security and anti-counterfeiting reliability, and its anti-counterfeiting efficiency is unmatched by traditional anti-counterfeiting technology, and has huge market potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of modified fibers, and in particular to a carbon dot-modified fluorescent fiber and a preparation method thereof. Background Art

[0002] The existence of counterfeit and inferior goods has a serious impact on society, forcing people to consider the prevention and identification of counterfeit and inferior goods, that is, anti-counterfeiting and identification. The purpose of anti-counterfeiting technology research is to provide methods for anti-counterfeiting and identification of counterfeit and inferior goods from a technical perspective, so that counterfeit and inferior goods cannot be released or can be quickly eliminated from the circulation field. The anti-counterfeiting information based on traditional anti-counterfeiting materials is easily separated from the film substrate, resulting in the loss of its anti-counterfeiting function.

[0003] Fluorescent fiber anti-counterfeiting technology is one of the core technologies of anti-counterfeiting materials. Fluorescent fiber has many characteristics such as controllable excitation spectrum, special nanomorphology and colorless and transparent appearance. Therefore, it shows excellent adaptability in anti-counterfeiting technology. It is an important anti-counterfeiting information marker. It can be used as an anti-counterfeiting substrate and is widely used in packaging anti-counterfeiting, military camouflage, road and high-altitude protective clothing, daily necessities, special photosensitive materials and information storage materials. Many fields. Fluorescent fibers developed by traditional technology will undergo fluorescence quenching when heated, so they cannot be applied to film packaging materials through the thermoplastic processing process, and are easily affected by external conditions, such as light, solvents, acids and alkalis, which cause them to lose their fluorescent properties and no longer have the function of fluorescent anti-counterfeiting. Therefore, the development of a new dual-wavelength fluorescent anti-counterfeiting fiber that is resistant to high temperatures, durable and highly stable has great application prospects and social benefits. Summary of the invention

[0004] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a carbon dot-modified fluorescent fiber and a preparation method thereof.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A carbon point modified fluorescent fiber is composed of the following raw materials in parts by weight: 0.1 to 1 part of carbon point modified fluorescent fiber; 1 to 20 parts of a compatibilizer; and 1 to 5 parts of a plasticizer.

[0007] Preferably, the carbon dot size of the carbon dot-modified fluorescent fiber is 5 to 10 nm, the fiber diameter of the carbon dot-modified fluorescent fiber is 22 to 28 μm, and the fiber length of the carbon dot-modified fluorescent fiber is 2 to 6 mm.

[0008] A method for preparing a carbon dot-modified fluorescent fiber comprises the following steps:

[0009] S1. Synthesis of carbon dots: 1-5 g of carbon source raw material for synthesizing carbon dots and 1-5 g of heteroatom doping raw material were mixed in 25 ml of deionized water to form a uniform solution, and then the solution was transferred to a 100 ml autoclave lined with polytetrafluoroethylene, and the autoclave was sealed and placed in an oven. The reaction temperature was set to 60-200° C., and the reaction time was 4-10 h. After the reaction was completed, the oven was closed, and the autoclave was cooled to room temperature to obtain a yellow-brown liquid;

[0010] S2. Separation of carbon dots: The product was transferred into deionized water, stirred evenly, and centrifuged at 5000-10000 rpm for 15-30 min to remove larger particulate impurities, and then filtered with a 0.1-10 um filter membrane to remove insoluble substances. The yellow supernatant was dialyzed for 24 h using a dialysis membrane, and the deionized water was replaced every 12 h to remove unreacted raw materials, and finally an aqueous solution of carbon dots with a size of 5-10 nm was obtained;

[0011] S3. Surface modification of fiber substrate: 2 g of fiber substrate with a length of 10 to 40 mm is placed in anhydrous ethanol for ultrasonic treatment for 0.5 to 3 h, then washed with deionized water, immersed in a 0.5 to 3 mol / L 2-methyl-1,5-diaminopentane solution, reacted in a 50 to 80°C water bath for 15 to 24 h for amino modification, the amino-modified fiber is taken out, and rinsed with deionized water, placed in 0.5 to 0.8 mol / L 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 0.1 to 0.2 mol / L N-hydroxysuccinimide and 0.5 to 1.5 mol / L sodium fatty acid methyl ester sulfonate buffer for cross-linking reaction, shaken in a shaker at 25°C for 2 to 5 h, rinsed with deionized water, and then placed in a refrigerator at a temperature of about 5°C for use;

[0012] S4. Preparation of fluorescent fiber: 1-5 g of surface-modified fiber and 5-40 mL of carbon dot solution are placed in an 80 mL high-pressure reactor with a polytetrafluoroethylene liner, and then 0-35 mL of deionized water is added to ensure that the fiber is immersed in the liquid. Subsequently, the high-pressure reactor is sealed and reacted in an oven at 60-200°C for 4-10 hours. After the reactor is cooled, the sample is taken out, filtered, and washed with deionized water for 5-10 times until the filtrate has no fluorescent reaction. The obtained fiber is dried in a vacuum drying oven at 40-60°C for 12-48 hours to finally obtain a fluorescent fiber with a length of 2-6 mm.

[0013] Preferably, the molecular cutoff of the dialysis membrane in step S2 is MWCO:1000.

[0014] Preferably, the carbon source raw material for synthesizing carbon dots in step S1 is one or a mixture of citric acid, acrylic acid, glucose, amino acids, lignin, starch, protein, polyurethane, polyacrylamide, and polyethylene glycol.

[0015] Preferably, the heteroatom doping raw material for synthesizing carbon dots in step S1 is one or a mixture of phenylenediamine, ethylenediamine, polyethyleneimine, o-phenylenediamine dimer, urea, ammonia water, amino acid, silane, 2-aminothiophenol, phosphoric acid, and melamine.

[0016] Preferably, the fiber base material in step S3 is one or a mixture of polyester fiber, polyacrylonitrile fiber, nylon fiber, aramid fiber, nylon, polyester, acrylic fiber, spandex, vinylon, polypropylene fiber, chloroprene fiber, and soybean fiber.

[0017] A carbon dot-modified fluorescent fiber is used as an anti-counterfeiting substrate in the preparation of packaging anti-counterfeiting, military camouflage, protective clothing for road and high-altitude operations, daily necessities, special photosensitive materials and information storage materials.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The anti-counterfeiting information markers in the present invention are difficult to separate, and fluorescent marking is performed by chemical attachment to obtain nano organic fluorescent fibers. The migration rate of the fluorescent substance used is extremely low, and existing analytical instruments cannot be used for sampling, separation and component analysis. It has extremely high anti-counterfeiting effectiveness in the field of thin film materials, further enhancing technical security and anti-counterfeiting reliability. Its anti-counterfeiting effectiveness is unmatched by traditional anti-counterfeiting technologies, and it has huge market potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is the Fourier transform infrared spectrum;

[0021] Figure 2 is the particle size distribution diagram of CDs;

[0022] Figure 3 is the average particle size diagram of CDs;

[0023] Figure 4 The fluorescence emission spectrum. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0025] A carbon point modified fluorescent fiber is composed of the following raw materials in parts by weight: 0.1 to 1 part of carbon point modified fluorescent fiber; 1 to 20 parts of a compatibilizer; and 1 to 5 parts of a plasticizer.

[0026] The carbon dot size of the carbon dot-modified fluorescent fiber is 5 to 10 nm, the fiber diameter of the carbon dot-modified fluorescent fiber is 22 to 28 μm, and the fiber length of the carbon dot-modified fluorescent fiber is 2 to 6 mm.

[0027] A method for preparing a carbon dot-modified fluorescent fiber comprises the following steps:

[0028] S1. Synthesis of carbon dots: 1-5 g of carbon source raw material for synthesizing carbon dots and 1-5 g of heteroatom doping raw material were mixed in 25 ml of deionized water to form a uniform solution, and then the solution was transferred to a 100 ml autoclave lined with polytetrafluoroethylene, and the autoclave was sealed and placed in an oven. The reaction temperature was set to 60-200° C., and the reaction time was 4-10 h. After the reaction was completed, the oven was closed, and the autoclave was cooled to room temperature to obtain a yellow-brown liquid;

[0029] S2. Separation of carbon dots: The product was transferred into deionized water, stirred evenly, and centrifuged at 5000-10000 rpm for 15-30 min to remove larger particulate impurities, and then filtered with a 0.1-10 um filter membrane to remove insoluble substances. The yellow supernatant was dialyzed for 24 h using a dialysis membrane, and the deionized water was replaced every 12 h to remove unreacted raw materials, and finally an aqueous solution of carbon dots with a size of 5-10 nm was obtained;

[0030] S3. Surface modification of fiber substrate: 2 g of fiber substrate with a length of 10 to 40 mm is placed in anhydrous ethanol for ultrasonic treatment for 0.5 to 3 h, then washed with deionized water, immersed in a 0.5 to 3 mol / L 2-methyl-1,5-diaminopentane solution, reacted in a 50 to 80°C water bath for 15 to 24 h for amino modification, the amino-modified fiber is taken out, and rinsed with deionized water, placed in 0.5 to 0.8 mol / L 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 0.1 to 0.2 mol / L N-hydroxysuccinimide and 0.5 to 1.5 mol / L sodium fatty acid methyl ester sulfonate buffer for cross-linking reaction, shaken in a shaker at 25°C for 2 to 5 h, rinsed with deionized water, and then placed in a refrigerator at a temperature of about 5°C for use;

[0031] S4. Preparation of fluorescent fiber: 1-5 g of surface-modified fiber and 5-40 mL of carbon dot solution are placed in an 80 mL high-pressure reactor with a polytetrafluoroethylene liner, and then 0-35 mL of deionized water is added to ensure that the fiber is immersed in the liquid. Subsequently, the high-pressure reactor is sealed and reacted in an oven at 60-200°C for 4-10 hours. After the reactor is cooled, the sample is taken out, filtered, and washed with deionized water for 5-10 times until the filtrate has no fluorescent reaction. The obtained fiber is dried in a vacuum drying oven at 40-60°C for 12-48 hours to finally obtain a fluorescent fiber with a length of 2-6 mm.

[0032] The molecular cutoff of the dialysis membrane in step S2 is MWCO:1000.

[0033] The carbon source raw material for synthesizing carbon dots in step S1 is one or a mixture of citric acid, acrylic acid, glucose, amino acids, lignin, starch, protein, polyurethane, polyacrylamide, and polyethylene glycol.

[0034] The heteroatom doping raw material for synthesizing carbon dots in step S1 is one or a mixture of phenylenediamine, ethylenediamine, polyethyleneimine, o-phenylenediamine dimer, urea, ammonia water, amino acid, silane, 2-aminothiophenol, phosphoric acid, and melamine.

[0035] The fiber substrate in step S3 is one or a mixture of polyester fiber, polyacrylonitrile fiber, nylon fiber, aramid fiber, nylon, polyester, acrylic fiber, spandex, vinylon, polypropylene fiber, chloroprene fiber, and soybean fiber.

[0036] A carbon dot-modified fluorescent fiber is used as an anti-counterfeiting substrate in the preparation of packaging anti-counterfeiting, military camouflage, protective clothing for road and high-altitude operations, daily necessities, special photosensitive materials and information storage materials.

[0037] Example 1

[0038] S1. Mix 1 g of citric acid and 3 g of polyethyleneimine in 25 ml of deionized water to form a uniform solution, then transfer the solution to a 100 ml autoclave lined with polytetrafluoroethylene, seal the autoclave tightly and place it in an oven, set the reaction temperature to 180°C, and the reaction time to 8 hours. After the reaction is completed, turn off the oven, and wait for the autoclave to cool to room temperature to obtain a yellow-brown liquid;

[0039] S2, the product was transferred to ultrapure water, stirred evenly and centrifuged at 10000rpm for 30min to remove larger particulate impurities, the filtrate was placed in a refrigerator for 12h, and then filtered with a 2um filter membrane to remove insoluble substances, and the yellow supernatant was dialyzed for 24h using a dialysis membrane (molecular cutoff MWCO: 1000), and the ultrapure water was replaced every 12h to remove unreacted raw materials, and finally a carbon dot aqueous solution with an average particle size of 5.2nm was obtained;

[0040] S3, put 2g of polyacrylonitrile fiber with a length of 10mm into anhydrous ethanol for ultrasonic treatment for 2h, then rinse with deionized water, immerse the rinsed fiber substrate into a 2mol / L 2-methyl-1,5-diaminopentane solution, react in a 50℃ water bath for 20h for amino modification, take out the amino-modified fiber, rinse with deionized water, and put it into 0.5mol / L 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 0.1mol / L N-hydroxysuccinimide and 1mol / L MES buffer for cross-linking reaction, shake in a shaker at 25℃ for reaction for 2h, rinse with deionized water, and then put it in a refrigerator at a temperature of about 5℃ for standby use;

[0041] S4. Place the surface-modified polyacrylonitrile fiber and 30 mL of carbon dot solution into an 80 mL high-pressure reactor lined with polytetrafluoroethylene, and then add 10 mL of deionized water to ensure that the fiber is immersed in the liquid. Subsequently, seal the high-pressure reactor and react in an oven at 180°C for 8 hours. After the reactor is cooled, take out the sample, filter it, and wash it with deionized water for 8 times until the filtrate has no fluorescent reaction. Dry the obtained fiber in a vacuum drying oven at 50°C for 12 hours to finally obtain a fluorescent fiber with a length of 7 mm.

[0042] Example 2

[0043] S1. Mix 5 g of acrylic acid and 2 g of urea in 25 mL of deionized water to form a uniform solution, then transfer the solution to a 100 ml autoclave lined with polytetrafluoroethylene, seal the autoclave tightly and place it in an oven, set the reaction temperature to 160 ° C, and the reaction time is 10 h. After the reaction is completed, turn off the oven, and wait for the autoclave to cool to room temperature to obtain a yellow-brown liquid;

[0044] S2, the product was transferred to ultrapure water, stirred evenly and centrifuged at 8000rpm for 30min to remove larger particulate impurities, the filtrate was placed in a refrigerator for 12h, and then filtered with a 2um filter membrane to remove insoluble substances, and the yellow supernatant was dialyzed for 24h using a dialysis membrane (molecular cutoff MWCO: 1000), and the ultrapure water was replaced every 12h to remove unreacted raw materials, and finally a carbon dot aqueous solution with an average particle size of 5.5nm was obtained;

[0045] S3. Place 2g of polyester fiber with a length of 20mm in anhydrous ethanol and ultrasonicate for 3h, then rinse with deionized water, immerse the rinsed fiber substrate in a 1.5mol / L 2-methyl-1,5-diaminopentane solution, and react in a 60℃ water bath for 15h for amino modification. Take out the amino-modified fiber, rinse it with deionized water, and then place it in 20mL of 15% (volume fraction) glutaraldehyde solution, shake it in a shaker at 30℃ for 4h, then rinse it with deionized water, and then place it in a refrigerator at a temperature of about 5℃ for standby use;

[0046] S4. The surface-modified polyester fiber and 25 mL of the carbon dot solution were placed in an 80 mL high-pressure reactor with a polytetrafluoroethylene liner, and 15 mL of deionized water was added to ensure that the fiber was immersed in the liquid. Subsequently, the high-pressure reactor was sealed and reacted in an oven at 160°C for 10 h. After cooling, it was filtered and washed until it was neutral. The obtained fiber was dried at 80°C for 12 h to finally obtain a fluorescent fiber with a length of 8 mm.

[0047] Example 3

[0048] S1. Mix 2 g of glucose and 5 g of ethylenediamine in 30 mL of deionized water to form a uniform solution, then transfer the solution to a 100 mL autoclave lined with polytetrafluoroethylene, seal the autoclave tightly and place it in an oven, set the reaction temperature to 140 ° C, and the reaction time is 6 h. After the reaction is completed, turn off the oven, wait for the autoclave to cool to room temperature, and obtain a yellow-brown liquid;

[0049] S2, the product was transferred to ultrapure water, stirred evenly and centrifuged at 10000 rpm for 25 min to remove larger particulate impurities, the filtrate was placed in a refrigerator for 12 h, and then filtered with a 1 um filter membrane to remove insoluble substances, and the yellow supernatant was dialyzed for 24 h using a dialysis membrane (molecular cutoff MWCO: 1000), and the ultrapure water was replaced every 12 h to remove unreacted raw materials, and finally a carbon dot aqueous solution with an average particle size of 5.4 nm was obtained;

[0050] S3, put 2g of soybean fiber with a length of 20mm into anhydrous ethanol for ultrasonic treatment for 1h, then rinse with deionized water, immerse the rinsed fiber substrate into a 2-methyl-1,5-diaminopentane solution with a concentration of 1.5mol / L, react in a 60℃ water bath for 15h for amino modification, take out the amino-modified fiber, rinse with deionized water and put it into 20mL of 25% (volume fraction) glutaraldehyde solution, shake in a shaker at 25℃ for reaction for 5h, then rinse with deionized water, and then put it in a refrigerator with a temperature of about 5℃ for standby use;

[0051] S4. Place the surface-modified soybean fiber and 20 mL of carbon dot solution into an 80 mL high-pressure reactor with a polytetrafluoroethylene liner, and then add 20 mL of deionized water to ensure that the fiber is immersed in the liquid. Subsequently, seal the high-pressure reactor and react in an oven at 175°C for 7 hours. After the reactor is cooled, take out the sample, filter it, and wash it with deionized water for 8 times until the filtrate has no fluorescent reaction. Dry the obtained fiber in a vacuum drying oven at 50°C for 12 hours to finally obtain a fluorescent fiber with a length of 6 mm.

[0052] Example 4

[0053] S1. Mix 4 g starch and 3 g melamine in 30 mL deionized water to form a uniform solution, then transfer the solution to a 100 mL autoclave lined with polytetrafluoroethylene, seal the autoclave tightly and place it in an oven, set the reaction temperature to 165 ° C, and the reaction time is 5 h. After the reaction is completed, turn off the oven, and wait for the autoclave to cool to room temperature to obtain a yellow-brown liquid;

[0054] S2, the product was transferred to ultrapure water, stirred evenly and centrifuged at 9000rpm for 30min to remove larger particulate impurities, the filtrate was placed in a refrigerator for 12h, and then filtered with a 2um filter membrane to remove insoluble substances, and the yellow supernatant was dialyzed for 24h using a dialysis membrane (molecular cutoff of MWCO: 1000), and the ultrapure water was replaced every 12h to remove unreacted raw materials, and finally a carbon dot aqueous solution with an average particle size of 5.5nm was obtained;

[0055] S3, put 2g of nylon fiber with a length of 20mm into anhydrous ethanol for ultrasonic treatment for 2h, then rinse with deionized water, immerse the rinsed fiber substrate into a 2.4mol / L 2-methyl-1,5-diaminopentane solution, react in a water bath at 80℃ for 20h for amino modification, take out the amino-modified fiber, rinse with deionized water and put it into 10mL 30% (volume fraction) glutaraldehyde solution, shake in a shaker at 25℃ for reaction for 5h, then rinse with deionized water, and then put it in a refrigerator at a temperature of about 5℃ for standby use;

[0056] S4. Place the surface-modified nylon fiber and 26 mL of carbon dot solution into an 80 mL high-pressure reactor with a polytetrafluoroethylene liner, and then add 14 mL of deionized water to ensure that the fiber is immersed in the liquid. Subsequently, seal the high-pressure reactor and react in an oven at 175°C for 8 hours. After the reactor is cooled, take out the sample, filter it, and wash it with deionized water for 8 times until the filtrate has no fluorescent reaction. Dry the obtained fiber in a vacuum drying oven at 50°C for 12 hours to finally obtain a fluorescent fiber with a length of 12 mm.

[0057] Example 5

[0058] S1. Mix 5g of polyurethane and 2g of ammonia water in 30mL of deionized water to form a uniform solution, then transfer the solution to a 100mL autoclave lined with polytetrafluoroethylene, seal the autoclave tightly and place it in an oven, set the reaction temperature to 170°C, and the reaction time to 9h. After the reaction is completed, turn off the oven, and wait for the autoclave to cool to room temperature to obtain a yellow-brown liquid;

[0059] S2. Transfer the product to ultrapure water, stir evenly and centrifuge at 10000rpm for 25min to remove larger particulate impurities. Place the filtrate in a refrigerator for 24h, filter with a 1um filter membrane to remove insoluble substances, and dialyze the yellow supernatant for 24h using a dialysis membrane (molecular cutoff MWCO: 1000). Replace ultrapure water every 12h to remove unreacted raw materials, and finally obtain a carbon dot aqueous solution with an average particle size of 8.6nm;

[0060] S3. Place 2g of 8mm long aramid fiber in anhydrous ethanol for 4h ultrasonic treatment, then rinse with deionized water, immerse the rinsed fiber substrate in a 3mol / L 2-methyl-1,5-diaminopentane solution, and react in an 80℃ water bath for 25h for amino modification. Take out the amino-modified fiber, rinse with deionized water, and place it in 20mL 30% (volume fraction) glutaraldehyde solution, shake it in a shaker at 25℃ for 5h, then rinse with deionized water, and then place it in a refrigerator at a temperature of about 5℃ for standby use;

[0061] S4. Place the surface-modified aramid fiber and 15 mL of carbon dot solution into an 80 mL autoclave lined with polytetrafluoroethylene, and then add 25 mL of deionized water to ensure that the fiber is immersed in the liquid. Subsequently, seal the autoclave and react in an oven at 165 ° C for 10 h. After cooling, filter and wash until neutral, and dry the obtained fiber at 80 ° C for 12 h to finally obtain a fluorescent fiber with a length of 6 mm.

[0062] The raw materials listed in the present invention, as well as the upper and lower limits and interval values ​​of the raw materials of the present invention, and the upper and lower limits and interval values ​​of the process parameters (such as temperature, time, etc.) can all realize the present invention, and the embodiments are not listed one by one here.

[0063] Reference Figure 1 , Figure 1 This is the infrared spectrum of the carbon dots prepared in Example 1 of the present invention. Figure 1(a), (b) and (c) are infrared spectra of polyacrylonitrile fiber before and after modification in Example 1 of the present invention, respectively. CDs, PANF and PANF-g-CDs were analyzed by Fourier infrared spectrometer, and it was found that there were obvious characteristic peaks at 1643cm-1, 1560cm-1, 1470cm-1 and 1389cm-1 in the infrared spectrum of CDs. According to relevant data, the peak at 1643cm-1 belongs to the C=O stretching vibration peak, the characteristic peak at 1560cm-1 belongs to the NH bending vibration peak, the peak at 1470cm-1 belongs to the C=H stretching vibration peak, and the peak at 1389cm-1 belongs to the CN stretching vibration peak. There are obvious characteristic peaks at 2956cm-1 and 1731cm-1 in the infrared spectrum of PANF. According to relevant data, the peak at 2956cm-1 belongs to the -C≡N stretching vibration peak, and the peak at 1731cm-1 belongs to the CH bending vibration peak. Compared with PAN, PAN-g-CDs showed two new characteristic peaks at 1479 cm-1 and 1271 cm-1, corresponding to the stretching vibrations of NH and NC on the secondary amide, respectively, which indicated that CDs were successfully grafted on PAN.

[0064] Reference Figure 2 , Figure 2 This is a particle size distribution diagram of the carbon dots prepared in Example 1 of the present invention. The particle size distribution test results measured by a dynamic light scattering instrument show that the carbon dots are evenly distributed, indicating that the carbon dots have good dispersibility in the aqueous solution and no agglomeration occurs. The particle size distribution of the carbon dots is narrow, the particle size is uniform, and the average particle size is 5.5nm.

[0065] Reference Figure 3 , Figure 3 (a) is the average particle size of the carbon dots prepared in Example 1 of the present invention, (b) is the average particle size of the carbon dots prepared in Example 2 of the present invention, (c) is the average particle size of the carbon dots prepared in Example 3 of the present invention, and (d) is the average particle size of the carbon dots prepared in Example 4 of the present invention. The particle size distribution test results measured by a dynamic light scattering instrument show that the average particle size of the carbon dots prepared in the present invention is about 5.5 nm, which is consistent with the particle size of common CDs (less than 10 nm).

[0066] Reference Figure 4 , Figure 4 (a) is the fluorescence emission spectrum of the carbon dots prepared in Example 1 of the present invention, and (b) is the fluorescence emission spectrum of the PANF-g-CDs prepared in Example 1 of the present invention. In order to compare the fluorescence properties of CDs and PANF-g-CDs, the fluorescence emission spectrum of the samples was tested with an excitation light of 365 nm. The results are shown in FIG. Figure 4As shown, it can be observed that CDs have an obvious emission peak at 440nm, and the emission peak of PANF-g-CDs appears at 454nm, which proves that both have fluorescent properties and have anti-counterfeiting uses. Compared with CDs, PANF-g-CDs are slightly red-shifted. This may be due to the change in the environment around PANF-g-CDs, which affects the CDs loaded on it.

[0067] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A carbon dot-modified fluorescent fiber, characterized in that: The preparation method of the carbon dot modified fluorescent fiber comprises the following steps: S1. Synthesis of carbon dots: 1-5 g of carbon source raw material for synthesizing carbon dots and 1-5 g of heteroatom doping raw material were mixed in 25 ml of deionized water to form a uniform solution, and then the solution was transferred to a 100 ml autoclave lined with polytetrafluoroethylene, and the autoclave was sealed and placed in an oven. The reaction temperature was set to 60-200° C., and the reaction time was 4-10 h. After the reaction was completed, the oven was closed, and the autoclave was cooled to room temperature to obtain a yellow-brown liquid; S2. Separation of carbon dots: The product was transferred into deionized water, stirred evenly, and centrifuged at 5000-10000 rpm for 15-30 min to remove larger particulate impurities, and then filtered with a 0.1-10 um filter membrane to remove insoluble substances. The yellow supernatant was dialyzed for 24 h using a dialysis membrane, and the deionized water was replaced every 12 h to remove unreacted raw materials, and finally an aqueous solution of carbon dots with a size of 5-10 nm was obtained; S3. Surface modification of fiber substrate: 2 g of fiber substrate with a length of 10 to 40 mm is placed in anhydrous ethanol for ultrasonic treatment for 0.5 to 3 h, then washed with deionized water, immersed in a 0.5 to 3 mol / L 2-methyl-1,5-diaminopentane solution, reacted in a 50 to 80°C water bath for 15 to 24 h for amino modification, the amino-modified fiber is taken out, and rinsed with deionized water, placed in 0.5 to 0.8 mol / L 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 0.1 to 0.2 mol / L N-hydroxysuccinimide and 0.5 to 1.5 mol / L sodium fatty acid methyl ester sulfonate buffer for cross-linking reaction, shaken in a shaker at 25°C for 2 to 5 h, rinsed with deionized water, and then placed in a refrigerator at 5°C for standby use; S4. Preparation of fluorescent fiber: 1-5 g of surface-modified fiber and 5-40 mL of carbon dot aqueous solution are placed in an 80 mL autoclave lined with polytetrafluoroethylene, and 10-35 mL of deionized water is added to ensure that the fiber is immersed in the liquid. Subsequently, the autoclave is sealed and reacted in an oven at 60-200° C. for 4-10 hours. After the autoclave is cooled, the sample is taken out, filtered, and washed with deionized water for 5-10 times until the filtrate has no fluorescent reaction. The obtained fiber is dried in a vacuum drying oven at 40-60° C. for 12-48 hours to finally obtain a carbon dot-modified fluorescent fiber with a length of 2-6 mm. The carbon dot size of the carbon dot-modified fluorescent fiber is 5 to 10 nm, the fiber diameter of the carbon dot-modified fluorescent fiber is 22 to 28 μm, and the fiber length of the carbon dot-modified fluorescent fiber is 2 to 6 mm; The molecular cutoff of the dialysis membrane in step S2 is MWCO:1000.

2. The carbon dot-modified fluorescent fiber according to claim 1, characterized in that: The carbon source raw material for synthesizing carbon dots in step S1 is one or a mixture of citric acid, acrylic acid, glucose, amino acids, lignin, starch, protein, polyurethane, polyacrylamide, and polyethylene glycol.

3. The carbon dot-modified fluorescent fiber according to claim 1, characterized in that: The heteroatom doping raw material for synthesizing carbon dots in step S1 is one or a mixture of phenylenediamine, ethylenediamine, polyethyleneimine, o-phenylenediamine dimer, urea, ammonia water, amino acid, silane, 2-aminothiophenol, phosphoric acid, and melamine.

4. The carbon dot-modified fluorescent fiber according to claim 1, characterized in that: The fiber base material in step S3 is one or a mixture of polyester fiber, polyacrylonitrile fiber, nylon fiber, aramid fiber, spandex, vinylon, polypropylene fiber, chlorofiber, and soybean fiber.

5. An application of the carbon dot-modified fluorescent fiber as described in any one of claims 1 to 4 as an anti-counterfeiting substrate in the preparation of packaging anti-counterfeiting, military camouflage, protective clothing for road and high-altitude operations, daily necessities, special photosensitive materials and information storage materials.